How to think like an entrepreneur - Broughton, Philip Delves, ....- (London : Macmillan, 2016)
Having the drive, ambition and inspiration to start a new business takes a particular mindset - no wonder we regard successful entrepreneurs as modern-day magic-makers. But what if that spirit and drive were applied outside the world of business startups? An entrepreneur seeks to build something from nothing; to take an inspired idea and make it a reality. How to Think Like an Entrepreneur explores what it takes to be a successful entrepreneur - the ability to disrupt the status quo, use design thinking to generate fresh perspectives, build resilience and leap forward from failure - and ultimately lead us to the heart of great entrepreneurial thinking; an understanding of our deepest human needs. By harnessing the passion, verve and creative thinking of an entrepreneur, you can improve your business and your life and relationships beyond it.
Keywords: Ondernemen